2016
DOI: 10.17059/2016-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Foreign Direct Investment Contribution in the Economic Development of Sverdlovsk Region and Russia

Abstract: УДК 339.9 Л. М. Капустина а) , Л. Липковá б) , О. Д. Фальченко а) а) Уральский государственный экономический университет

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Establishing the main determinants of economic growth is one of the key research questions of interest to scientists since the time of Smith (2007). There are a large number of works that study the factors and causes of the development of economic systems, among which are basic indicators such as human capital (Mankiw et al, 1992;Basu and Bhattarai, 2012;Ahuru and James, 2015); scientific and technological progress (Goncharova and Bezdenezhnykh, 2018;Zhou and Luo, 2018), digitalization and innovation (Dvas and Dubolazova, 2018;Rudskaya and Rodionov, 2018;Akinwale et al, 2020), effective institutions and investments (Tebaldi and Mohan, 2008;Kapustina et al, 2016;Karpenko, 2019;Kudryavtseva et al, 2020), natural resources and favorable geographic location (Alkhathlan, 2013;Tukan et al, 2015;Bhattarai and Taloba, 2017;Ushakov et al, 2019); spatial effects (Bernat, 1996;Niebuhr, 2003).…”
Section: Literature Viewmentioning
confidence: 99%
“…Establishing the main determinants of economic growth is one of the key research questions of interest to scientists since the time of Smith (2007). There are a large number of works that study the factors and causes of the development of economic systems, among which are basic indicators such as human capital (Mankiw et al, 1992;Basu and Bhattarai, 2012;Ahuru and James, 2015); scientific and technological progress (Goncharova and Bezdenezhnykh, 2018;Zhou and Luo, 2018), digitalization and innovation (Dvas and Dubolazova, 2018;Rudskaya and Rodionov, 2018;Akinwale et al, 2020), effective institutions and investments (Tebaldi and Mohan, 2008;Kapustina et al, 2016;Karpenko, 2019;Kudryavtseva et al, 2020), natural resources and favorable geographic location (Alkhathlan, 2013;Tukan et al, 2015;Bhattarai and Taloba, 2017;Ushakov et al, 2019); spatial effects (Bernat, 1996;Niebuhr, 2003).…”
Section: Literature Viewmentioning
confidence: 99%
“…Early GRP evaluation method on the basis of relevant regional statistics [3] allows to anticipate the appearance of the indicator in press by 1-1.5 years. The pertinent challenge for Sevastopol is the attraction of investments, including foreign ones, as their flow is limited by sanctions, this is why the publications on the following topics are of interest: direct foreign investment influence on the economy of the receiving country and region [4]; measuring the contribution of direct foreign investments on production in Russian regions and interregional inequality by per capita real GRP [5]; investment attractiveness of regions as a key factor of encouraging foreign investments [6] and their impact on the Russian economy in terms of regions [7]; the interconnection between foreign investment and sanctions [8]; influence of investment process media coverage on the inflow of direct foreign investment into the region [9]; analysis of investment attractiveness evaluation methods by economic activities in regions [10]; influence of investments on social and economic development of a region [11], with options for assessment of the multiplying effects, that resulted from investments into certain industries and identification of growth focal points in regions. From our point of view, the proposed methods and simulations presented in the article will allow the regional authorities to conduct a more evidence-based development policy for the Russian regions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Carkovic and Levine (2002) found that FDI inflows have no influence on economic growth. Kapustina, Lipkova and Falchenko (2016) also found that FDI's impact on economic growth in the Sverdlovsk region and in the Russia is weak. Instead, they found that the most important factor that has a positive influence on the growth of gross regional product and gross domestic product is represented by domestic investment in fixed assets.…”
mentioning
confidence: 99%